ANALISIS PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE MODIFIKASI PADA PERUSAHAAN BUMN SEKTOR FARMASI - Dinni Wildiastri (EKSYDA: Jurnal Studi Ekonomi Syariah, 2022)
This study aims to test the prediction of insolvency in the BUMN’s formation company PT Indo Farma (Persero) Tbk. The Altman Z-Score modification method used to see the prediction of company bankcrupty in the 2015 to 2019 periods. The analysis technique used is the predictive model of Altman Z-Score modification. Wich it applies four variables X1 (Working Capital to Total Assets), X2 (Retained Earnings to Total Assets), X3 (Earning Before Interest and Tax to Total Assets), X4 (Market Value of Equity to Total Liabilities). It has the formula Z” = 6,56X1 + 3,26X2 + 6,72X3 + 1,05X4. Within the Z-Score assessment criteria Z-Score < 1,1 is categorized bankrupt company. 1,1 < Z-Score < 2,6 is categorized in a “grey area”. And Z-Score > 2,6 is categorized as a very healthy company. During observations point start from 2014 to 2019 point out that PT Indo Farma (Persero) Tbk categorized was “grey area” because its Z-Score was not reached up 2,6. Although in the first year of observations this categorized company was “healthy”, but overall it was categorized position in “grey area” because value of Z-Score was below 2,6.